Irinotecan Plus Mitomycin C as Second-Line Chemotherapy for Advanced Gastric Cancer Resistant to Fluoropyrimidine and Cisplatin: A Retrospective Study - Ogawa, Kohei (Hindawi Publishing Corporation, 2012)
Background. S-1 plus cisplatin has been established to be standard first-line chemotherapy for advanced gastric cancer in Japan. The optimal second-line treatment refractory to S-1 plus cisplatin remains unclear. Methods. We retrospectively studied the efficacy, toxicity, and survival of irinotecan plus mitomycin C in patients with advanced gastric cancer refractory to a fluoropyrimidine plus cisplatin. Results. Twenty-four patients were studied. Prior chemotherapy was S-1 plus cisplatin in 15 patients, S-1 plus cisplatin and docetaxel in 8, and 5-fluorouracil plus cisplatin with radiotherapy in 1. The overall response rate was 17.4%. The median overall survival was 8.6 months, and the median progression-free survival was 3.6 months. Grade 3 or 4 toxicities included leukopenia (33%), neutropenia (50%), anemia (33%), thrombocytopenia (4%), anorexia (13%), diarrhea (4%), and febrile neutropenia (13%). Conclusion. A combination of irinotecan and mitomycin C is potentially effective in patients with advanced gastric cancer refractory to a fluoropyrimidine plus cisplatin.